UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA MASA PANDEMI COVID-19 DI SDMU AHMAD DAHLAN BRAJA SELEBAH - Bety Budiasih (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2020)
This article aims to describe the efforts made by SDMU Ahmad Dahlan Braja Selebah in improving student learning outcomes during the Covid 19 Pandemic. The learning system carried out during the Covid19 pandemic currently requires teachers to be more active and creative by utilizing social media as a medium of learning. The research method used in this research is descriptive qualitative data collection methods through observation, interviews and documentation. The results showed that the teacher chose the right learning method and the school supported it by facilitating the use of existing media as a means of delivering distance learning material as well as conducting regular evaluation of learning. The positive contribution in this study is intended to inform the managers of educational institutions that learning activities during the Covid-19 period can be improved by fulfilling distance learning sarpras and choosing appropriate learning methods and material presentation.